'Is Fox News a Breach of Human Rights?': The News Media's Immunity from the Guiding Principles on Business and Human Rights. Issue 2 (14th April 2016) - JOSEPH, Sarah
Abstract: The business and human rights debate has essentially bypassed the media industry. This article addresses that gap in the debate by applying the Guiding Principles on Business and Human Rights to the media. Application of human rights responsibilities to the media in accordance with the Guiding Principles is significantly complicated by the existence of media rights of freedom of expression. It is argued that the application of the Guiding Principles to the media industry leaves significant scope for it to be involved with serious and systemic human rights violations. This conclusion indicates that the Guiding Principles are an inadequately theorised tool for dealing with human rights responsibilities of the media. It may reveal deeper flaws in the Guiding Principles, which extend to industries other than the media. At the least, a dialogue between the human rights community and the media industry must commence in order to work out how human rights might apply in the context of the responsibilities of one of the world's most important and powerful industries.